Cognitive decline in a patient with anti-glutamic acid decarboxylase autoimmunity; case report - Takagi Masahito; Yamasaki Hiroshi; Endo Keiko; Yamada Tetsuya; Kaneko Keizo; Oka Yoshitomo; Mori Etsuro (BMC Neurology, 2011)
Abstract Background Glutamic acid decarboxylase (GAD) is the rate-limiting enzyme for producing γ-aminobutyric acid, and it has been suggested that antibodies against GAD play a role in neurological conditions and type 1 diabetes. However, it is not known whether dementia appears as the sole neurological manifestation associated with anti-GAD antibodies in the central nervous system. Case presentation We describe the clinical, neuropsychological, and neuroradiological findings of a 73-year-old female with cognitive dysfunction and type 1A diabetes. Observation and neuropsychological studies revealed linguistic problems, short-term memory disturbance, and frontal dysfunction. MRI showed no significant lesion except for confluent small T2-hyperintensity areas localized in the left basal ganglia. 18F-fluorodeoxy glucose-positron emission tomography (FDG-PET) and 123I-N-isopropyl-p-iodoamphetamine-single photon emission computed tomography (IMP-SPECT) studies showed bifrontal hypometabolism and hypoperfusion. Immunomodulating therapy with intravenous high-dose immunoglobulin resulted in no remission of the cognitive symptoms. Conclusions Cognitive dysfunction may develop as an isolated neurological manifestation in association with type 1A diabetes and anti-GAD autoimmunity. A systematic study with extensive neuropsychological assessment is indicated in patients with type 1 diabetes and anti-GAD autoimmunity.